Unveiling the dynamic drivers: phase separation’s pivotal role in stem cell biology and therapeutic potential - Pei Lin; Yunfan Lin; Ye Lu; Xu Chen; Zihao Zhou; Xinyuan Zhao; Li Cui (Stem Cell Research & Therapy)
Abstract Phase separation is fundamental for cellular organization and function, profoundly impacting a range of biological processes from gene expression to cellular signaling pathways, pivotal in stem cell biology. This review explores the primary types of phase separation and their mechanisms, emphasizing how phase separation is integral to maintaining cellular integrity and its significant implications for disease progression. It elaborates on current insights into how phase separation influences stem cell biology, discussing the challenges in translating these insights into practical applications. These challenges stem from the complex dynamics of phase separation, the need for advanced imaging techniques, and the necessity for real-time, in situ analysis within living systems. Addressing these challenges through innovative methodologies and gaining a deeper understanding of the molecular interactions that govern phase separation in stem cells are essential for developing precise, targeted therapies. Ultimately, advancing our understanding of phase separation could transform stem cell-based therapeutic approaches, opening up novel strategies for disease treatment and advancements in regenerative medicine.